The effects of work social support and career adaptability on career satisfaction and turnover intentions - Karatepe, Osman M.; Olugbade, Olusegun A. (Cambridge Univ Press, 2017)
Applying career construction theory, this study develops and tests a research model that investigates whether career adaptability mediates the effect of work social support on career satisfaction and turnover intentions. Data obtained from frontline hotel employees with a 2-week time lag in three waves in Nigeria were used to assess the previously mentioned relationships. The results from structural equation modeling suggest that work social support boosts career adaptability and career satisfaction, while it mitigates turnover intentions. Surprisingly, the results suggest that career adaptability triggers turnover intentions, while it has no bearing on career satisfaction. The results further suggest that career adaptability partially mediates the relationship between work social support and turnover intentions.
Keywords: career adaptability; career satisfaction; Nigeria; turnover intentions; work social support